Hypercatabolism and Anti-catabolic Therapies in the Persistent Inflammation, Immunosuppression, and Catabolism Syndrome - Zhang, Jinlin; Luo, Wenchen; Miao, Changhong; Zhong, Jing (Frontiers in Nutrition, 2022)
Owing to the development of intensive care units, many patients survive their initial insults but progress to chronic critical illness (CCI). Patients with CCI are characterized by prolonged hospitalization, poor outcomes, and significant long-term mortality. Some of these patients get into a state of persistent low-grade inflammation, suppressed immunity, and ongoing catabolism, which was defined as persistent inflammation, immunosuppression and catabolism syndrome (PICS) in 2012. Over the past few years, some progress has been made in the treatment of PICS. However, most of the existing studies are about the role of persistent inflammation and suppressed immunity in PICS. As one of the hallmarks of PICS, hypercatabolism has received little research attention. In this review, we explore the potential pathophysiological changes and molecular mechanisms of hypercatabolism and its role in PICS. In addition, we summarize current therapies for improving the hypercatabolic status and recommendations for patients with PICS.